Marie Hazard - Hazard, Marie 1994-; Baudin, Arno; García-Baudin, Angela (Zolo Press, 2022)
Marie Hazard writes on the loom, imprinting her vibrant textiles with fragments of text and pieces of photographs that "register the dance of being in and moving through the world." Her debut monograph gathers some one-hundred-and-fifty works woven and nine exhibitions made between 2018 and 2022, alongside a modular essay by art historian Olivier Berggruen and a conversation with artist George Tiger Liu
Keywords: Hazard, Marie -- 1994-; Bildband